Landscapes on the edge: river intermittency in a warming world - McLeod,J; Whittaker,AC; Bell,RE; Hampson,GJ; Watkins,SE; Brooke,SAS; Rezwan,N; Hook,J; Zondervan,JR; Ganti,V; Lyster,SJ (Geology, 2024)
Sediment transport in rivers is not steady through time. Highly intermittent river systems, which only transport bedload during the most significant flow events, are particularly sensitive to changes in climate and precipitation patterns. People and landscapes can be vulnerable to fluvial processes, and quantifying river intermittency is critical for assessing landscape response to projected changes in precipitation extremes due to climate change. We generated new constraints on recent to modern fluvial intermittency factors—the frequency at which bedload is mobilized in a river—based on field measurements in the Corinth Rift, Greece, and Holocene sediment accumulation rates. Results reveal some of the lowest documented intermittency factors to date, showing Mediterranean rivers can transport an entire annual sediment load in a rare storm event. Coupling intermittency calculations with historical flood and precipitation data indicates these rivers transport bedload during one storm every ∼4 yr, associated with rainfall >50 mm/d, and subsequent floods; this hydroclimate is typical across the Mediterranean region. Furthermore, climate models predict precipitation extremes will increase across Europe, and the frequency of events that surpass thresholds of sediment transport will increase significantly, potentially causing sediment loads to double by 2100 CE. As the area of arid land likely to host intermittent rivers also increases, sensitive landscapes are on the edge of significant geomorphic change, driven by global warming.